Estudio de pre factibilidad para la generación de la línea de créditos verdes de producción limpia y sostenible del Banco Solidario - Flores Terán, Franklin Daniel (2023)
At present, environmental problems produced by industrial processes and agricultural activities can be evidenced, which have been increasing worldwide with the invasion and exploitation of natural resources to meet the needs and supply of a population that continues to grow. Because of this it is important to carry out the development of a proposal of green credits in order to know its theoretical feasibility and its impact in generating an awareness of environmental care, encouraging through economic benefits a new model of clean and sustainable production. To determine the pre-feasibility of green credits, an investigation of the existing green credits, their characteristics and the segment of customers to which it is focused, was carried out. Following this, a survey was conducted to a significant sample of beneficiaries that have agricultural activities located in the canton Otavalo. A methodological design was carried out in which the approval of green credits can be validated, taking into account environmental and social criteria, generating a qualification tool applicable for enterprises with a projection to a clean and sustainable production. As a result of this research, a baseline of agricultural enterprises in the city of Otavalo was raised, which in a 71% have developed sustainable projects and apply agro-productive practices friendly to the environment, thus, the feasibility of the creation and application of green credits was also determined because there is interest on the part of the beneficiaries, being green credits an alternative that through economic benefits that financial institutions are able to grant will encourage the care of the environment within a key segment of the population such as the agro-productive sector.